ANALYSIS OF FINANCIAL PERFORMANCE USING LIQUIDITY RATIO, SOLVENCY RATIO, ACTIVITY RATIO, PROFITABILITY RATIO IN PHARMACEUTICAL SUB-SECTOR MANUFACTURING COMPANIES ON THE INDONESIA STOCK EXCHANGE FOR THE 2018-2020 PERIOD IN DKI JAKARTA - Syntha Noviyana; Angelia Sherlita Febriyola; Komsi Koranti (Jurnal Syntax Transformation, 2023)
Financial performance is the result or achievement that has been achieved by the company's management in carrying out its function of managing company assets effectively during a certain period. Financial performance is very much needed by companies to find out and evaluate the level of success of the company based on the financial activities that have been carried out. Indonesian Securities for the period 2018-2020. In this study, the types of data used were qualitative and quantitative data with secondary data sources. The data collection procedure in this study is to analyze the financial statements that have been documented using a descriptive and comparative qualitative approach. Based on the results of this study, PT Darya Varia Laboratoria Tbk, PT Kalbe Farma Tbk, PT Kimia Farma Tbk, PT Merck Tbk and PT Pyridam Farma Tbk have had good financial performance at certain financial ratios. The company also has poor financial performance on profitability ratios.